2021
DOI: 10.1126/sciadv.abh2037
|View full text |Cite
|
Sign up to set email alerts
|

Multiform antimicrobial resistance from a metabolic mutation

Abstract: A critical challenge for microbiology and medicine is how to cure infections by bacteria that survive antibiotic treatment by persistence or tolerance. Seeking mechanisms behind such high survival, we developed a forward-genetic method for efficient isolation of high-survival mutants in any culturable bacterial species. We found that perturbation of an essential biosynthetic pathway (arginine biosynthesis) in a mycobacterium generated three distinct forms of resistance to diverse antibiotics, each mediated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 81 publications
5
31
0
Order By: Relevance
“…7h ), known members of the whiB7 regulon in Mtb 35 . Thus, we hypothesized that partial loss-of-function ettA alleles may promote drug resistance by stalling translation and constitutively upregulating the whiB7 stress response, in essence mimicking the effects of translation stress caused by ribosome inhibitors to activate whiB7 53 . Consistent with this hypothesis, whiB7 and regulon genes 35 were constitutively upregulated in the ettA -Gly41Glu Mtb mutant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7h ), known members of the whiB7 regulon in Mtb 35 . Thus, we hypothesized that partial loss-of-function ettA alleles may promote drug resistance by stalling translation and constitutively upregulating the whiB7 stress response, in essence mimicking the effects of translation stress caused by ribosome inhibitors to activate whiB7 53 . Consistent with this hypothesis, whiB7 and regulon genes 35 were constitutively upregulated in the ettA -Gly41Glu Mtb mutant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with many previously identified antibiotic-tolerant mutants, our transcriptomic analysis of SDM-tolerant mutants revealed upregulation of the SOS response and biofilm formation along with dramatic downregulation of metabolic processes 4 , 14 , 24 , 51 , 52 . Metabolic mutations have not only been implicated in tolerance, but also in resistance, as shown by recent studies which found mutations in central carbon metabolism, energy metabolism, and biosynthetic pathway genes associated with antibiotic resistance in in vitro evolved strains and in clinical isolates 28 , 53 . A clearer, more comprehensive picture of cellular pathways that can lead to tolerance and resistance is emerging, which will be helpful in developing more robust antibiotic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Even though tolerance and bacterial metabolism are inherently linked 16 , 24 , the effect of antibiotic metabolism dependence on tolerance evolution has not been investigated, and it is unknown whether tolerance evolves similarly to all antibiotics, whether SDM or WDM. However, as metabolic dormancy protects against antibiotic lethality 16 , 25 , 26 and in vitro antibiotic evolution experiments have yielded tolerance-inducing mutations in metabolic genes 4 , 27 , 28 , there is a strong likelihood that antibiotic metabolism dependence will be a key determinant of the rate at which tolerance evolves.…”
Section: Introductionmentioning
confidence: 99%
“…A myriad number of synthetic derivatives of this azole have been reported for their a nticancer [ 15 , 16 ], antibacterial [ 17 ], antiviral [ 18 ], and several other therapeutic properties [ 19 ]. In our research on azole derivatives as potent antibacterial [ 20 , 21 , 22 ] and antineoplastic agents [ 23 , 24 , 25 ], we found pyrazole-derived hydrazones are potent growth inhibitors of A. baumannii [ 21 , 26 ] and the aniline derivatives of pyrazoles are potent growth inhibitors of Gram-positive bacteria [ 22 , 27 ]. In this article, we report data on the antimicrobial activities, and the modes of action, of a series of hit compounds ( Figure 1 ) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%